Modifikasi Zeolit Alam Menjadi ZSM-5 Sebagai Penjerap CO2 - Gregorius Prima Indra Budianto (Eksergi, 2021)
Biogas is a product of the bio-decomposition process in anaerobic conditions. Methane (CH4) and carbon dioxide (CO2) are the compounds of biogas that act in determining the quality of biogas. When the CH4 level is high, the biogas will have a high caloric value; conversely, the increased CO2 levels result in low biogas heating value. One effort to purify biogas is the adsorption process using natural zeolite. Natural zeolite should be modified into ZSM-5 because it has a greater pore diameter than natural zeolite. It is expected that the increase of the efficiency of CO2 adsorption is more significant than natural zeolite. ZSM-5, which is altered from natural zeolite, will be compared to the effectiveness of CO2 adsorption compared to natural zeolite